Sistem Pengendalian Internal Sebagai Pemoderasi Pengaruh Integrasi e-Planning dan eBudgeting Terhadap Pencegahan Korupsi - Iriyani, Istirokhana; Mutmainah, Siti (E-Jurnal Akuntansi; Vol 34 No 1 (2024), 2024)
This research aims to examine the effect of the integration of e-planning and e-budgeting on preventing corruption with the internal control system as a moderating variable. Another objective is to analyze the direct influence of each indicator of the e-planning and e-budgeting integration variables, namely Standard Unit Price (SSH), Standard Cost Analysis (ASB), APBD budgeting, and supervision of corruption prevention. The research sample includes 112 local governments on the island of Java in 2021 and 2022. Data analysis uses the WarpPLS 7.0 application. The research results prove that the integration of e-planning and e-budgeting has a positive effect on preventing corruption. The internal control system has been proven to weaken the relationship between e-planning and e-budgeting integration and corruption prevention. ASB indicators, APBD budgeting and supervision have a positive effect, while SSH have a negative effect on preventing corruption. APBD budgeting is the most dominant indicator, while ASB is the weakest indicator in influencing corruption prevention. It is hoped that the practical implications of this research will serve as input for the government in formulating more appropriate policies for action plans to prevent corruption. Keywords: Corruption Prevention; E-Planning And E-Budgeting; Internal Control System